Gelatin Nanoparticle‐Injectable Platelet‐Rich Fibrin Double Network Hydrogels with Local Adaptability and Bioactivity for Enhanced Osteogenesis. Issue 5 (29th January 2020) - Mu, Zhixiang; Chen, Kaiwen; Yuan, Shuai; Li, Yihan; Huang, Yuanding; Wang, Chao; Zhang, Yang; Liu, Wenzhao; Luo, Wenping; Liang, Panpan; Li, Xiaodong; Song, Jinlin; et al.
Abstract: Bone healing is a dynamic process regulated by biochemical signals such as chemokines and growth factors, and biophysical signals such as topographical and mechanical features of extracellular matrix or mechanical stimuli. Hereby, a mechanically tough and bioactive hydrogel based on autologous injectable platelet‐rich fibrin (iPRF) modified with gelatin nanoparticles (GNPs) is developed. This composite hydrogel demonstrates a double network (DN) mechanism, wherein covalent network of fibrin serves to maintain material integrity, and self‐assembled colloidal network of GNPs dissipates force upon loading. A rabbit sinus augmentation model is used to investigate the bioactivity and osteogenesis capacity of the DN hydrogels. The DN hydrogels adapt to the local environmental complexity of bone defects, i.e., accommodate the irregular shape of the defects and withstand the pressure formed in the maxillary sinus during animal's respiration process. The DN hydrogel is also demonstrated to absorb and prolong the release of the bioactive growth factors stemming from iPRF, which could have contributed to the early angiogenesis and osteogenesis observed inside the sinus. This adaptable and bioactive DN hydrogel can achieve enhanced bone regeneration in treating complex bone defects by maintaining long‐term bone mass and withstanding the functional mechanical stimuli. Abstract : Double network hydrogels adapt to irregular shaped bone defects and withstand the pressure formed in the maxillary sinus during animal's respiration process. This hydrogel is also demonstrated to absorb and prolong the release of growth factors stemming from injectable platelet‐rich fibrin, which could have contributed to the early angiogenesis and osteogenesis inside the sinus.